2015
DOI: 10.1055/s-0034-1398596
|View full text |Cite
|
Sign up to set email alerts
|

Psychosoziale Arbeitsbedingungen und mentale Gesundheit der Babyboomergeneration

Abstract: For the regarded group of the German babyboomers, employees at the threshold to higher working age, it is clearly shown that psychosocial working conditions are related to mental health. Since this group still has to work up to 18 years given a statutory retirement age of 67, psychosocial working conditions should rather be in the focus of occupational safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
1
Order By: Relevance
“…In regard to possible mental and emotional strains, our results show that while the Baby Boomers have to cope with the need to stay updated and feel the pressure of social-environmental expectations, they lack a deeper understanding of the online activities of their children and grandchildren. Psychosomatic research supports this observation: If still employed, Baby Boomers feel a high pressure in competing with younger colleagues [49]. Targeted coping strategies are needed for this generation, regardless of whether they are still employed or not.…”
Section: Baby Boomersmentioning
confidence: 90%
“…In regard to possible mental and emotional strains, our results show that while the Baby Boomers have to cope with the need to stay updated and feel the pressure of social-environmental expectations, they lack a deeper understanding of the online activities of their children and grandchildren. Psychosomatic research supports this observation: If still employed, Baby Boomers feel a high pressure in competing with younger colleagues [49]. Targeted coping strategies are needed for this generation, regardless of whether they are still employed or not.…”
Section: Baby Boomersmentioning
confidence: 90%
“…Several studies have shown the association between adverse psychosocial factors and various outcomes including personal consequences like diabetes [7] , musculoskeletal disorders [8] , work-family conflict [9] , adverse lifestyle [10] , and mental health [11] as well as organizational adverse effects such as absenteeism [12] , intent to leave the job [13] , also, in some studies, an association is found between occupational stress and occupational accidents [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Jüngst identifizierte eine Befragung von über 500 Entscheidern aus dem deutschsprachigen Raum das Managen von Veränderungen und den Umgang mit wachsender Komplexität als die größten Herausforderungen von Führungskräften [1]. Generell werden unter Berufstätigen heute erhöhte Stress-und Burnout-Level im Kontext eines Überlastungsempfindens sowie die Zunahme von Arbeitsunfähigkeiten durch psychische Diagnosen berichtet [2][3][4][5][6][7]. Angesichts dessen erfährt in jüngster Zeit das Konzept der Achtsamkeit u. a. zur Stressregulation eine besondere Beachtung und das nicht allein im therapeutischen Umfeld, sondern auch in beruflichen Kontexten [8,9].…”
Section: Introductionunclassified